CONTENT AND FACTORS OF THE INVESTMENT POWER OF THE REGION - Xodjibaeva Iqbola Valiyevna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article examines the content of the process of forming the investment potential of the region and its factors.